2009
DOI: 10.1261/rna.1306009
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide evolutionary analysis of the noncoding RNA genes and noncoding DNA of Paramecium tetraurelia

Abstract: The compact genome of the unicellular eukaryote Paramecium tetraurelia contains noncoding DNA (ncDNA) distributed into >39,000 intergenic sequences and >90,000 introns of 390 base pairs (bp) and 25 bp on average, respectively. Here we analyzed the molecular features of the ncRNA genes, introns, and intergenic sequences of this genome. We mainly used computational programs and comparative genomics possible because the P. tetraurelia genome had formed throughout whole-genome duplications (WGDs). We characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
(52 reference statements)
1
10
0
Order By: Relevance
“…The snoRNA USE (5′-AAACCCATAA) (Figure 1C) identified in this study was identical to the one identified previously upstream of Tetrahymena snRNA genes and in ncRNA genes of Paramecium (26,52). It was found upstream of 22 out of 27 intergenic monocistronic snoRNAs.…”
Section: Discussionsupporting
confidence: 83%
“…The snoRNA USE (5′-AAACCCATAA) (Figure 1C) identified in this study was identical to the one identified previously upstream of Tetrahymena snRNA genes and in ncRNA genes of Paramecium (26,52). It was found upstream of 22 out of 27 intergenic monocistronic snoRNAs.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, ~ 98% of P. tetraurelia introns are 20–30 nt in size, with a mean of 25 nt. A handful of significantly larger introns, ~ 80 nt in size, contain snoRNAs [ 18 ]. We therefore decided to train the highly configurable EuGene annotation software [ 12 ] for Paramecium , using gene models completely confirmed by RNA-Seq coverage (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the RWGD coincides with the explosion of speciation events that gave rise to the P. aurelia complex of 15 sibling species, while the old WGD (OWGD) probably occurred before the divergence of Paramecium and Tetrahymena. In addition, due to a very low rate of large-scale chromosomal rearrangements in P. tetraurelia, the sequenced Paramecium genome provides a unique system to identify an unprecedented large number of WGD paralogs of different ages and to study the mechanisms of genome evolution consequences on gene duplication (Chen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%